Provision of quality and certification intermediaries - Gian Luigi Albano; Alessandro Lizzeri (Fondazione Eni Enrico Mattei (FEEM), 1997)
If buyers do not observe the quality of a product and production of quality is costly, market allocations can be very inefficient. Certification intermediaries are institutions that provide information about quality to buyers. The amount of information in the market determines the incentives that producers have to provide high quality goods. In this paper, we model information revelation as a strategic variable of intermediaries. The amount of disclosed information is shown to deeply influence both the intermediary's profits and the distribution of quality produced in equilibrium. We show that a monopoly intermediary will provide noisy signals of quality and that the quality produced in equilibrium is the same as the one that would be chosen by a monopsonistic buyer who optimally designs a mechanism. Efficiency is increased by the intermediary but less quality is produced in equilibrium than under complete information.
Keywords: C72; D82; L15; 330; Information revelation; Disclosure rule; Certification; Produktqualität; Warenkennzeichnung; Auskunftspflicht; Asymmetrische Information; Spieltheorie; Theorie